(untitled) (Scientific Journal of Research Studies in Future Management, 2025)
In recent years, small and medium-sized enterprises (SMEs) have been recognized as key drivers of economic growth and innovation in Iran. One of the major determinants of their sustainability and competitiveness is the application of practical marketing training delivered by skilled instructors. This study aims to assess the role of marketing instructors’ competencies in enhancing innovation and competitiveness of SMEs within Iran’s entrepreneurial ecosystem. Using a descriptive–analytical approach, real data were collected from 120 SMEs located in Tehran, Isfahan, and Khorasan Razavi provinces. Data were gathered through the standardized Marketing Instructors’ Skill Questionnaire (2019) and the OECD Innovation Index, and analyzed using path analysis in Smart PLS software. The results revealed significant positive relationships between instructors’ teaching, communication, and technological skills and the level of innovation in products, services, and processes (total path coefficient = 0.68, p<0.01). Indirect effects were also found through the mediating role of organizational learning culture and market-oriented thinking in boosting competitiveness. The findings suggest that designing training programs based on hybrid skillsets (marketing knowledge, technology, and creative pedagogy) can serve as an effective policy tool to strengthen entrepreneurship development and SME performance in Iran.